Correlation of Inflammatory Biomarkers and White Blood Cell Count withCAD Severity and Mortality in Acute Coronary Syndrome Patients - Ravi Kiran S; Sudarshan K; S S Sawakar; Suresh S R (RGUHS Journal of Medical Sciences)
Background Acute Coronary Syndrome ACS encompassing ST-elevation myocardial infarction STEMI non-ST-elevation myocardial infarction NSTEMI and unstable angina is primarily driven by coronary artery disease CAD and inflammation. Inflammatory markers such as white blood cell WBC count and C-reactive protein CRP have emerged as potential predictors of adverse outcomes in ACS.Objectives This study aims to evaluate the relationship between baseline WBC count and clinical outcomes in ACS patients specifically focusing on short-term mortality. Additionally it examines whether WBC count independently predicts outcomes when considered alongside other biomarkers like CRP.Methods This cross-sectional study was conducted at a General Hospital from August 2022 to January 2024. It involved 110 patients presenting with chest pain. Each patient underwent ECG TROP I CRP and WBC assessments. ACS cases were categorized into STEMI NSTEMI and unstable angina.Results Our findings indicate that baseline leukocyte count and CRP levels are significantly associated with poor outcomes in ACS patients. Elevated WBC count and CRP were statistically significant predictors of shortterm mortality suggesting their potential utility in identifying high-risk patients early in the disease course.Conclusion This study demonstrates a strong association between baseline WBC count CRP and the severity of CAD in patients presenting with ACS. Elevated inflammatory markers are significant predictors of shortterm mortality underscoring the importance of including WBC and CRP assessments in initial ACS evaluations to guide risk stratification and treatment planning.